Socioeconomic inequalities in outcomes, experiences and treatment among adults consulting primary care for a musculoskeletal pain condition: a prospective cohort study - Dahai Yu; Kelvin P Jordan; Jonathan C Hill; Emma Parry; Simon Wathall; James Bailey; Lindsey Brown; George M Peat; Stephen Dent; Clare Thompson; Ruth Haines; John Haines; et al. (BMJ Open, 2025)
Objectives To estimate the direction and magnitude of socioeconomic inequalities in outcome, experience and care among adults consulting for a musculoskeletal pain condition.Design Multicentre, prospective observational cohort with repeated measures at three waves (baseline, 3 months and 6 months after index consultation).Setting 30 general practices in North Staffordshire and Stoke-on-Trent, England.Participants 1875 consecutive, eligible, consenting patients, aged 18 years and over, presenting with a relevant SNOMED CT-coded musculoskeletal pain condition between September 2021 and July 2022.Interventions Standard care.Primary and secondary outcome measures Primary outcome was patient-reported pain and function using the Musculoskeletal Health Questionnaire (MSK-HQ score, 0–56). Secondary outcomes were patient experience (overall dissatisfaction with consultation experience, dichotomised) and an indicator of care received (opioid prescription within 14 days of index consultation). Using multilevel models, we examined inequalities in primary and secondary outcomes by area deprivation (Index of Multiple Deprivation derived from patient residential postcode), before and after adjusting for sociodemographic and survey administration variables, clinical case-mix and selected practice-level covariates.Results Compared with patients from the least deprived neighbourhoods, patients from the most deprived neighbourhoods had significantly poorer MSK-HQ scores at baseline (mean 22.6 (SD 10.4) vs 27.6 (10.1)). At 6 months, the inequality gap in MSK-HQ score widened (difference in mean score after adjustment for all covariates: 1.94; 95% CI: −0.70 to 4.58). Opioid prescription was more common for patients living in the most deprived neighbourhoods (30% vs 19%; fully adjusted OR: 0.69; 95% CI: 0.44 to 1.08). Only 6% of patients overall reported being dissatisfied with their consultation. Analysis of multiply imputed data produced a similar pattern of findings to complete-case analysis.Conclusions Substantial inequalities in the chronicity, severity and complexity of musculoskeletal pain problems are already present at the time of accessing care. Inequalities in pain and function do not reduce after accessing care and may even widen slightly.Trial registration number ISRCTN18132064; Results.